Experimental Research on the Dynamic Response of Floating Structures with Coatings Subjected to Underwater Explosion - Feng Xiao; Yong Chen; Yu Wang; Hongxing Hua; Dawei Zhu (Shock and Vibration)
This paper presents an experimental investigation into the dynamic response of three free floating stiffened metal boxes with protective coatings subjected to underwater explosion (UNDEX). One box was kept intact while the other two were, respectively, covered with monolithic coatings and chiral honeycomb coatings. Three groups of live fire tests with different attack angles and stand-off distances were conducted. The acceleration on the stiffener and strain peak on the bottom hull were selected as the major comparative criterions. Test results show that the impulse transmitted to the structure at the initial stage can be reduced, owing to the coating flexibility and fluid-structure interaction mechanism. Consequently, the acceleration peaks induced by both shock wave and bubble pulse were reduced. The shock environment can be more effectively improved by honeycomb coating when compared with monolithic coating. Most of the strain peaks decreased to a certain extent, but some of them were notably manifested, especially for honeycomb coating. The test affirms the fact that soft coating can cause stress concentration on the shell that is in direct contact with the coating due to the impedance mismatch between the interfaces of materials. A softer rubber coating induces a greater magnitude of strain.